Avaliação da operacionalização da atenção primária à saúde frente à pandemia da covid-19 nos municípios de Imperatriz e São Luís- MA - BRITO, Paula dos Santos (2022)
The study aimed to evaluate the operationalization of Primary Health Care (PHC) in the face of the COVID-19 pandemic. A cross-sectional study carried out simultaneously with 843 adult users and with 99 primary care physicians and nurses, in the municipality of Imperatriz and in the capital São Luís, in the state of Maranhão. Data were collected in December 2020 from the Epidemiological Surveillance Service of Maranhão and through interviews with participants from December 2020 to January 2022, with the help of the adapted instrument Primary Care Assessment Tool (PCATool) versions for users adults, and medical professionals and nurses. A descriptive analysis of the sociodemographic variables regarding the participants' profile was performed. To calculate the score of each attribute, data was transformed into a scale from 0 to 10 according to the PCATool, which was classified as High performance (≥ 6.6) or Low performance (<6.6). To assess the distribution of normality of numerical variables, the Kolmogorov-Smirnov test was used and, based on this result, the Mann-Whitney test was applied, with a significance level of 5% (p < 0.05) and their respective 95% confidence intervals. Data were processed using the Statistical Package for Social Sciences software, version 24.0. Study approved by the Research Ethics Committee of the Federal University of Maranhão under opinion 4,256,677. Most users were from Imperatriz (55.99%), female (59.79%), brown (43.42%), married (43.42%), high school (46.50%) and high school age of 43.30 years. The sample of professionals was predominantly composed of women (81.82%), the professional category of nurse (76.77%), with a specialist degree (82.83%) and a mean age of 35 years. The average time of training was 6 years, with an average of 4 years in PHC. The PHC Essential Score attributed by users was 4.52 and by doctors and nurses 6.54. The General Score attributed by users and by doctors and nurses was 4.89 and 6.66, respectively. In the users' evaluation, only the Information System component of the Attention Coordination attribute achieved a high performance score, with values of 7.50 in Imperatriz and 7.60 in São Luís. From the perspective of medical professionals and nurses, the essential attribute First Contact Access had the lowest overall score, with an average of 5.22. The attributes Coordination of care, in the Integration of care component, and Community Orientation were assigned as low performance in both investigation scenarios. When comparing the scores attributed by professionals and users, a statistical association (p <0.05) was found for: Longitudinality, Coordination of care, Integrality, Family Orientation. This study showed that there is a significant difference in the perception of professionals and users regarding the operationalization of PHC. In the general assessment of users, both municipalities had low performance and in the general assessment of professionals, only Imperatriz had high performance. These data can support actions in the planning and improvement of strategies by local and national managers to strengthen PHC in the face of the COVID-19 pandemic and future public health emergencies.